MANAJEMEN HUBUNGAN MASYARAKAT DALAM DAKWAH DAN PENDIDIKAN ISLAM: PEMANFAATAN MEDIA DIGITAL UNTUK MENINGKATKAN CITRA INSTITUSI KAHFI BBC MOTIVATOR SCHOOL - Tubagus Wahyudi; Rokimin Rokimin; Hambali Hambali; Muhammad Mamduh Nuruddin; Milki Aan (Hijri, 2025)
This study aims to examine Public Relations (PR) management in Islamic preaching and education through the use of digital media to enhance the institutional image of KAHFI BBC Motivator School. With the development of digital technology, Islamic educational institutions, including KAHFI BBC, face the challenge of adapting to these changes to strengthen their institutional image. This research employs a quantitative approach using survey methods, and data analysis is conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The variables analyzed include digital communication strategies, frequency and consistency of digital content, stakeholder involvement, and the institutional image of Islamic educational institutions as the dependent variable. The findings show that the frequency and consistency of digital content and communication strategies in digital media significantly influence the institutional image. However, stakeholder involvement in managing digital media did not have a significant impact. The R-Square value of 0.4158 indicates that the effective use of digital media can improve the institutional image, although other factors also contribute. This study also demonstrates that integrating Islamic values with modern PR strategies through digital media can have a positive impact on enhancing institutional reputation. The findings offer practical recommendations for other Islamic educational institutions to optimize the use of digital media in building their positive image in the digital era.